Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/joop.12403
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic view on work‐related perfectionism: Antecedents at work and implications for employee well‐being

Abstract: Little is known about the role of perfectionism in employees' daily work. Our study aimed to provide a fine-grained view on perfectionism in work life by examining daily work-related perfectionism in terms of perfectionistic strivings and concerns. Drawing on whole trait theory and the DYNAMICS IN WORK-RELATED PERFECTIONISM How to cite this article: Mohr, M., Venz, L., & Sonnentag, S. (2022). A dynamic view on work-related perfectionism: Antecedents at work and implications for employee well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…The results from the exploratory analyses reflect this pattern of findings for all sleep components. We integrate the assumptions of CAPS theory and the SDM, and complement research on daily fluctuations of perfectionism (Mohr et al, 2022). Thus, not only is dynamic perfectionism shaped by stressful work experiences but also perfectionism as a fairly stable trait shapes these experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the exploratory analyses reflect this pattern of findings for all sleep components. We integrate the assumptions of CAPS theory and the SDM, and complement research on daily fluctuations of perfectionism (Mohr et al, 2022). Thus, not only is dynamic perfectionism shaped by stressful work experiences but also perfectionism as a fairly stable trait shapes these experiences.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, the study contributes to and extends the occupational health psychology and personality psychology literature in three important ways: First, concerning the literature on perfectionism, we broaden the knowledge of mechanisms in the work (i.e., stressors) and nonwork area (i.e., recovery) that explains the different associations between perfectionism and sleep quality by examining time pressure and detachment as a potential serial mechanism. Drawing on CAPS theory, we complement the dynamic perspective from previous research, which demonstrated that situational cues, such as time pressure, may trigger daily fluctuations of perfectionism (Mohr et al, 2022). Thus, we enhance knowledge of how perfectionism shapes work experiences and is mutually shaped by these experiences.…”
Section: The Stressor–detachment Model As a Theoretical Frameworkmentioning
confidence: 97%
“…Previous studies have shown that irrational thoughts can objectively undermine individual performance [27]. In addition, they have been linked with high and strict evaluation standards (e.g., perfectionism) and one's work overinvestment due to feelings of internal inadequacy and guilt (e.g., workaholism), which usually result in reduced well-being and distress [7,[28][29][30][31]. For this reason, we argue that irrational beliefs may be harmful to wellbeing at work because they may hinder employees' perceptions of their own performance and, more specifically, the degree to which they are matching performance expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability 2023, 15, x FOR PEER REVIEW 3 of 18 [7,[28][29][30][31]. For this reason, we argue that irrational beliefs may be harmful to well-being at work because they may hinder employees' perceptions of their own performance and, more specifically, the degree to which they are matching performance expectations.…”
Section: Introductionmentioning
confidence: 99%